2021
DOI: 10.1002/jcla.24075
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of HLA gene polymorphisms in Romanian patients with chronic renal insufficiency undergoing renal transplantation

Abstract: Over the last few decades, an impressive number of studies have established strong associations between certain diseases and individuals carrying particular HLA alleles. 1 Although these studies have proven a strong association between HLA and certain diseases (eg ankylosing spondylitis, type 1 diabetes and narcolepsy), the effector mechanisms underlying HLA-disease associations remain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…These results are in agreement with those of Noureen et al [26]. The HLA-A*11 allele was also positively associated with ESRD in a previous study performed by Maruntelu et al in the Romanian population [27]. However, the results of our study differed from those of Cao et al, who described an association between allele HLA*24 and ESRD [5].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with those of Noureen et al [26]. The HLA-A*11 allele was also positively associated with ESRD in a previous study performed by Maruntelu et al in the Romanian population [27]. However, the results of our study differed from those of Cao et al, who described an association between allele HLA*24 and ESRD [5].…”
Section: Discussionsupporting
confidence: 92%
“…One of the first studies was carried out by Guja et al [ 53 ] who highlighted strong predisposing and protective associations of HLA-DQB1 in type 1 diabetes mellitus. Recently, our research group has identified HLA class I and II alleles that predispose patients to chronic renal failure [ 54 ] or increase the risk of developing hepatitis B [ 55 ]. In another work by Maruntelu et al [ 56 ], they also showed that the occurrence of celiac disease is closely associated to the HLA-DQA1*05:01, HLA-DQB1*02:01, and HLA-DQB1*02:02 allele expression in Romanian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they identified a higher prevalence of protective alleles, which could explain the low incidence of this disease in the Romanian population. Recently, our team identified certain HLA class I and class II alleles with predisposing effects in patients with CRI [ 39 ]. Alleles such as HLA-B ∗ 40, HLA-C ∗ 12, and HLA-DRB1 ∗ 14 were found to be particularly predisposing to CRI in the Romanian population, in contrast to previous findings.…”
Section: Discussionmentioning
confidence: 99%